THE EFFECT OF LEADERSHIP STYLE ON WORK DISCIPLINE AT THE PT.STATE ELECTRICITY COMPANY (PLN) PERSERO MAKALE AREA, TANA TORAYA REGENCY - Chrismesi Pagiu; Rati Pundissing (Jurnal Ekonomi, 2023)
This study aims to determine the effect of leadership style on work discipline at the State Electricity Company (PLN) Persero Makale Area, Tana Toraja Regency. The type of research used is descriptive quantitative. Data collection techniques were carried out using observation, questionnaires, and documentation. The data sources used are primary data obtained by direct interviews with related parties concerned with the problem under study and from questionnaires. The analysis technique used is simple linear regression and significance test using the SPSS version 26 program. Based on the results of calculations with the t-test on the leadership variable, the result is counted as 4,454 > table 2,04227 and a significance value of 0.000 <0,05, so it can be concluded that the leadership variable affects work discipline. The results of the coefficient of determination show that 39,8% of leadership style influences work profession, and the remaining 60,2% is explained in other variables not included in the study, while the correlation between the loan interest rate variable and the demand for productive business loans is 0,631, meaning that the relationship between solid variable.